Effects of Job Stress, Work Culture and Against the Performance of Lecturers and Work Associations as Intervening Variables at the University of Ibnu Sina - Mulyadi Mulyadi; Nelly Chandrawati Manalu; Andi Hidayatul Fadillah; Firdaus Hamta (IAIC International Conference Series, 2021)
The purpose of this study is to determine the causality of work stress relationships, work ties to the performance of lecturers and payments at Ibnu Sina University. The research was carried out using quantitative methods and statistical package analysis tools for Social Sciences (SPSS) 25 with respondents surveyed 99 samples from 132 lecturer populations and research using questionnaires. The results of the study that (1) work stress directly does not significantly influence the performance of lecturers at the University of Ibnu Sina; (2) work culture directly has a significant effect on lecturer performance at Ibnu Sina University; (3) work ties directly have insignificant effect on the performance of lecturers at Ibnu Sina University; (4) work stress does not have a significant effect on lecturers' performance through work ties at Ibnu Sina University; (5) work culture has no significant effect on the performance of lecturers through work ties at the Ibnu Sina University.